An Educational Intervention to Train Professional Nurses in Promoting Patient Engagement: A Pilot Feasibility Study - Barello, Serena; Graffigna, Guendalina; Pitacco, Giuliana; Mislej, Maila; Cortale, Maurizio; Provenzi, Livio (Frontiers in Psychology, 2017)
Introduction Growing evidence recognizes that patients who are motivated to take an active role in their care can experience a range of health benefits and reduced healthcare costs. Nurses play a critical role in the effort to make patients fully engaged in their disease management. Trainings devoted to increase nurses’ skills and knowledge to assess and promote patient engagement are today a medical education priority. To address this goal, we developed a program of nurse education training in patient engagement strategies (NET-PES).This paper presents pilot feasibility study and preliminary participants outcomes for NET-PES. Methods: This is a pilot feasibility study of a 2-session program on patient engagement designed to improve professional nurses’ ability to engage chronic patients in their medical journey; the training mainly focused on passing patient engagement assessment skills to clinicians as a crucial mean to improve care experience. A pre-post pilot evaluation of NET-PES included 46 nurses working with chronic conditions. A course specific competence test has been developed and validated to measure patient engagement skills. The design included self-report questionnaire completed before and after the training for evaluation purposes. Participants met in a large group for didactic presentations and then they were split into small groups in which they used role-play and case discussion to reflect upon the value of patient engagement measurement in relation to difficult cases from own practice. Results: Forty-six nurses participated in the training program. The satisfaction questionnaire showed that the program met the educational objectives and was considered to be useful and relevant by the participants. Results demonstrated changes on clinicians’ attitudes and skills in promoting engagement. Moreover, practitioners demonstrated increases on confidence regarding their ability to support their patients’ engagement in the care process. Conclusions: Training nurses in this area is feasible and accepted and might have an impact on their ability to engage patients in the chronic care journey. Due to the limitation of the research design, further research is needed to assess the effectiveness of such a program and to verify if the benefits envisaged in this pilot are maintained on a long-term perspective and to test results.